Prophylactic Use of Fluconazole in Very Premature Infants - Zhang, Deshuang; Xie, Dongke; He, Na; Wang, Xiaoling; Dong, Wenbin; Lei, Xiaoping (Frontiers in Pediatrics, 2021)
Objective: To evaluate the efficacy, safety, and fungal sensitivity of prophylactic fluconazole use in very premature infants. Methods: We performed a retrospective historical comparative analysis of 196 very premature infants (113 in the prophylaxis group and 83 in the rescue group). The incidence of nosocomial fungal infection (NCFI) and pathogenic fungi, their drug sensitivity, and the minimum inhibitory concentration (MIC) of fluconazole were compared between the two groups. We also analyzed differences in short-term adverse outcomes, such as drug-induced liver or renal function disruption, fungal-attributable death, bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP), periventricular leukomalacia (PVL), intraventricular hemorrhage (IVH), and necrotizing enterocolitis (NEC), between the groups. The effects of the prophylactic fluconazole strategy on NCFI and short-term adverse outcomes were assessed by multivariate logistic regression. Results:Candida albicans (46.7%) and Candida glabrata (43.3%) were the main culprit pathogens causing NCFI. The incidence of NCFI was significantly lower in the prophylaxis group than in the rescue group (15.9 vs. 45.8%, P < 0.001). However, fewer fungi were completely sensitive to fluconazole (40 vs. 85%, P < 0.05) and the MIC of fluconazole was higher [16.0 (3.5 ~ 16.0) vs. 3.0 (1.0 ~ 8.0) μg/ml, P < 0.001] in the prophylaxis group than in the rescue group. Compared with the rescue group, the prophylaxis group had a lower risk of NCFI (adjusted OR 0.25; 95% CI 0.11, 0.55). Additionally, the prophylaxis group had significantly lower risks of combined outcomes (one or more complications, such as BPD, ROP needing interventions, PVL/IVH (grade > 2), NEC stage ≥2, and fungal-attributable death) (adjusted OR 0.44; 95% CI 0.21, 0.92). There was no significant difference in serum alanine transferase (ALT), aspartate transaminase (AST), creatinine (Cr), or direct bilirubin (DBIL) levels between the two groups. Conclusions: Fluconazole prophylaxis reduced NCFI and improved combined clinical outcomes in very premature infants, with no increased risks of serious short-term adverse side effects; however, the MIC of fluconazole showed significant increases. Therefore, further optimization of preventive strategies is necessary to maintain the sensitivity of fluconazole against fungal isolates.